Perancangan Aplikasi Secure Message Berbasis Smartphone (Studi Kasus Di Dinas Komunikasi Dan Informasi Kabupaten Takalar) - Aminuddin, Rosihan; Rais, Muhammad (Department of Electrical Engineering, University of Patria Artha, 2020)
This study aims to develop software by building a secure message application based on a smartphone or android. This application was developed using a prototyping model. The prototyping model consists of several stages: the first stage, namely the gathering of needs, the second stage of building prototyping, the third stage of coding the system, the fifth stage of testing the system. The results obtained in this study are an Android-based secure message application that can improve performance for anyone who uses an Android-based smartphone. For testing using blackbox, whitebox and expert validation, this application is suitable for use.